A planning model for creative industry zone-producer of clothes used as cultural tourism product Case study in the area of Tuan Kentang 15 Ulu Palembang - Primadella Primadella (IPTEK Journal of Proceedings Series, 2017)
Creative industry has a significant contibution in increasing economy because it can create positive atmosphere in tourism sector. The area of Tuan Kentang 15 Ulu - Palembang is one of creative industry zones from fashion subsector which produces Jumputan and Tajung clothes which are known by many people. As one of tourism products based on creative industry, the area of Tuan Kentang has possessed five charateristics of creative tourism, i.e, tourists become part of the tourism progress, the existence of participative learning, interactive, informal, limited products, and has something to do with the local people. However, there were so many constraints, such as lack of planning and facilities needed for tourism development in this area. This influences the number of visitors coming to this area. By doing this research, there will be model of planning for creative industry zone which produces a number of clothes as an effort to improve the quality of the area and culture in Palembang. This research used descriptive qualitative and quantitative as a method in analyzing. The products of tourism by using scoring range for the products through participative place making approach. There were some stages in analyzing the data, that is by using likert scale and SWOT analysis. The result of this research composed factors and facilities that used to be created in a creative industry area, which could determine and develop the planning for tourism area based on creative industry in Indonesia.